Substantive Maturity in ‘Āishah’s Marriage - Moch. Nurcholis; Mohammad Fajrul Falah Afandi; Mayla Aflahul Karimah; Abdul Latif (Jurnal Hikmatuna, 2021)
This study aims to analyze the substantive maturity of Aishah's marriage, where based on the hadist of the Prophet, Aishah married the Prophet at the age of 6 years and started married at the age of 9 years. The information contained in the hadith is closely related to the issue of child marriage in the mainstream discourse of protecting children's rights, particularly the rules for limiting the age of marriage that have been implemented so far. The method used in analyzing the above problems is descriptive with an approach to the history of Islamic law. This study notes that 'Aishah marriage has fulfilled the substantive maturity element, both physically which is marked by reproductive readiness and non-physical with indicators of intellectual maturity. Besides that, the age of marriage 'Aishah is done by determining the element of purpose (al-á¸¥adf) in the form of maturity quality and the component of means (al-wasÄ«lah) in the form of age. Thus, this element has significance for religious legality guarantees related to the rules for the age limit of marriage that apply in Muslim countries.